ECONOMIC MECHANISM FOR STIMULATING DEVELOPMENT AND STRUCTURAL REFORM OF THE SMALL AND MEDIUM BUSINESS SECTOR INTHE CONDITIONS OF UKRAINE’S EUROPEAN INTEGRATION - VASYLTSIV, Taras; MAHAS, Denys (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines aspects of state policy to stimulate the development of small and medium-sized businesses in Ukraine (at the regional level). The issues of state policy to stimulate the development and structural reform of the small and medium-sized business sector in war conditions, as well as the accelerated European integration of Ukraine actualized by it, are analyzed. The purpose of the study is to substantiate the provisions of the economic mechanism for stimulating the development and structural reform of the small and medium-sized business sector in the context of Ukraine’s European integration. The general logic of the formation of the economic mechanism of the state policy for stimulating development in the small and medium-sized business sector is determined. Conclusions are drawn regarding the quality of the economic mechanism formed in the regions of Ukraine to stimulate the development and structural reform of small and medium-sized businesses in the region in the context of Ukraine’s European integration. The scientific novelty of the research results lies in the further development of theoretical and methodological and methodological and applied provisions on the formation and implementation of state policy instruments for structural reforms in the country’s small and medium-sized business sector. The applied significance of the research results lies in the development of a number of decisions and recommendations that regional state authorities and local governments can implement in order to achieve the desired structural changes and shifts in the business sector of the regional socio-economic system.